Estudos de associação entre locos SSR e componentes da produção em arroz (Oryza sativa L.) - Bueno, Clistiane dos Anjos Mendes (2010)
Rice is consumed by more than half of the world population. The expectation of substantial population growth and consequently the increase of the consumption has demontrated that the present rice production will not supply the future’s demand. As a result, studies that aim at the increase of the yield must be prioritized by scientific co&unity. Aiming to identify genomic regions related to grain yield and its component traits (panicle number per meter, grain panicle number and hundred grain mass), it was carried out the associative mapping analysis. The analysis of association used two types of SSR markers: a) structural genome derived markers, and b) transcriptome derived markers, i.e. developed from transcripts from marker-anchored genomic regions previously related to yield and its components from 27 different QTL maps already published. The associative mapping methodology used included the whole genome scanning and candidate genes approaches. The molecular characterization used 186 accessions from Embrapa Rice Core Collection (ERiCC), whereas 76 accessions from lowland system of cultivation, and 113 upland system of cultivation. The experimental design was the randomized block with 4 repetitions, and included the cultivars BR Irga 409, Metica 1 and BRS Caiapó as controls. It were evaluated the following traits: Panicle number per meter (NPM), panicle (NGP), Hundred grain mass (PCG) and productivity. The 186 markers were genotyped by 29 transcript-derived SSR markers and 86 SSR markers derived from structural genome. For the irrigated accessions was verified positive correlation for panicle number per meter and productivity (0,2424; p<0,01) and by productivity and hundred grain mass (p<0,05; 0,1457) and negative correlation for panicle number per meter and grain number per panicle (-0,457; p<0,01). For the upland accessions it was observed positive correlation for grain number per panicle and productivity (0,4243; p<0,01). Negative correlations were observed for panicle number per meter and hundred grain weight (p<0,01; -0,2114). Based on 44 SSR markers developed in this work, 181 alelles were detected, an average of 5.5 alelles per locus, average PIC of 0.44 and 25 private alleles. The analysis with 115 SSR markers identified 43 significant associations for grain number per panicle considering the cultivation system upland and three associations for lowland system; 7 significant associations for panicle number per meter for lowland system, and 9 were significant for upland cultivation systems; 14 associations were significant for hundred grain mass in lowland system of cultivarion, and 43 were significant for upland system of cultivarion; 3 associations were significant for grain yield in upland system of cultivarion. The association analysis identified 61 SSR markers consistently associated to yield and its components. It were detected 33 associations statiscally significant to one or more traits, which validated the previous results obtained by QTL mapping. The markers RM125, RM152 e Q69JE3 showed the higher number of associations per trait. The association productivity and PCG, and NCP, respectively, were previously found in the literature. The markers associated to the evaluated traits permit to initiate a scientific program to identify the candidate genes and to proceed the marker assisted selection The accessions CNA0001107, CNA0005478, CNA0010533, CNA0003287, IR 36, CNA0003602, CNA0006413, CNA0006174, CNA0003289, CNA0002253, CNA0004098, CNA0001416, CNA0003490 e CNA0000994 showed the highest number of favorable alleles considering 16 the markers associated to yield and its components. The identified accessions from this work as having the higher number of favorable alleles from the evaluated traits will be recommended to be used as genitors in Brazilian rice breeding programs. The mixed approaches to the associative mapping used in the present work was interesting to permit that, even using a low marker density, in couple with the linkage disequilibrium found in rice, some previously mapped markers from QTL analyses were again associated to traits evaluated in field experiments. This strategy can be used to other traits of interest for rice, such as drought and cold tolerance, and disease resistance.